Shelf Life of Minced Pork in Vacuum-Adsorbed Carvacrol@Natural Zeolite Nanohybrids and Poly-Lactic Acid/Triethyl Citrate/Carvacrol@Natural Zeolite Self-Healable Active Packaging Films - Vassilios K. Karabagias; Aris E. Giannakas; Nikolaos D. Andritsos; Areti A. Leontiou; Dimitrios Moschovas; Andreas Karydis-Messinis; Apostolos Avgeropoulos; Nikolaos E. Zafeiropoulos; Charalampos Proestos; Constantinos E. Salmas (Antioxidants, 2024)
Enhancing food preservation and safety using environmentally friendly techniques is urgently needed. The aim of this study was to develop food packaging films using biodegradable poly-L-lactic acid (PLA) as biopolymer and carvacrol (CV) essential oil as an antioxidant/antibacterial agent for the replacement of chemical additives. CV was adsorbed onto natural zeolite (NZ) via a new vacuum adsorption method. The novel nanohybrid CV@NZ with a high CV content contained 61.7%wt. CV. Pure NZ and the CV@NZ nanohybrid were successfully dispersed in a PLA/triethyl citrate (TEC) matrix via a melt extrusion process to obtain PLA/TEC/xCV@NZ and PLA/TEC/xNZ nanocomposite films with 5, 10, and 15%wt CV@NZ or pure NZ content. The optimum resulting film PLA/TEC/10CV@NZ contained 10%wt. CV@NZ and exhibited self-healable properties, 22% higher tensile strength, 40% higher elongation at break, 45% higher water barrier, and 40% higher oxygen barrier than the pure PLA/TEC matrix. This film also had a high CV release content, high CV control release rate as well as 2.15 mg/L half maximal effective concentration (EC50) and 0.27 mm and 0.16 mm inhibition zones against Staphylococcus aureus and Salmonella enterica ssp. enterica serovar Typhimurium, respectively. This film not only succeeded in extending the shelf life of fresh minced pork, as shown by the total viable count measurements in four days but also prevented the lipid oxidation of fresh minced pork and provided higher nutritional values of the minced meat, as revealed by the heme iron content determination. It also had much better and acceptable sensory characteristics than the commercial packaging paper.